Impact of Age and Gender on Plasma N-Terminal Pro-B-Type Natriuretic Peptide - Al-Muhanna, Fatima F.; Al-Dejeli, Amina A. B. (Medical Science Journal for Advance Research, 2024)
Background: Age has a significant impact on the body, which may affect plasma concentrations of NT-proBNP. (e.g., increased fibrosis and heart stiffness, worse renal function, and lower lean body mass). Elevated NT-proBNP levels are commonly reported in advanced age groups, even in seemingly healthy individuals. On the other hand, Some studies suggest that Women have larger plasma concentrations of natriuretic peptides than men. Objective: In a population-based research, we wanted to look at how age and gender affected the plasma N-terminal pro -B-type natriuretic peptide (NT.proBNP) concentration in patients with non-ST elevation acute coronary syndrome (NSTE-ACS) with negative coronary artery disease (CAD) confirmed by percutaneous coronary intervention (PCI). Methods: Electrocardiogram (ECG), serum troponin I, 2D echocardiography, plasma NT.proBNP, and PCI were performed on 48 Iraqi patients from Al-Najaf Center for Cardiac Surgery and Transcatheter Therapy/ Al-Sader Teaching Hospital, department of coronary intervention who have non-ST elevation acute coronary syndrome NSTE-ACS with negative CAD (< 50% arterial blockage) seen by PCI. This group of people had sinus rhythm, no renal or pulmonary illness, normal systolic function, and no valvular abnormality. Results: Within this group, Age differences existed in NT.proBNP distribution. Age-related increases in NT.proBNP were statistically significant. Regarding gender, our results had no statistically significant difference in NT.proBNP between males and females. Conclusions: Our study concluded that Plasma NT.proBNP level increases with age among patients with NSTE-ACS and negative CAD, while there is no significant difference in this hormone between males and females.